Effects of Coupling Water and Fertilizer on Agronomic Traits, Sugar Content and Yield of Sugarcane in Guangxi, China - Weixiong Wu; Wuxiang Fu; Juha M. Alatalo; Zhanxia Ma; Yang Bai (Agronomy, 2022)
This work is a contribution to applied water and fertilizer coupling efforts aiming at increasing crop productivity on sugarcane plantations through the analysis of average cane yields obtained following main agronomic traits in growth and sugar content of plantations, in order to improve irrigation scheduling practices. A field experiment was carried out, testing drip irrigation (D), with four levels (0%, 50%, 100% and 150%) of water (W) and four levels (0%, 50%, 100% and 150%) of fertilizer (F) with three replicates. Rain-fed crop (neither irrigation nor fertilizer DW0F0) and manpower irrigation were included as the control (W1F1). The effects of water and fertilizer on agronomic traits (plant high, stem diameter, effective stem number and single stem weight), sugarcane yield and sugar content were studied in Guangxi (southwest China) from 2018–2020. Compared with W1F1, the agronomic traits were higher under DW1F1 treatment; for sugar content, the benefit of the combined treatment was W0.5F0; for sugarcane yield, the best treatment was DW1F1, followed by DW1.5F1. To obtain maximum sugar yield, it is recommended to apply a N fertilizer dose of 292 kg ha−1, K2O fertilizer 146.55 kg ha−1 and P2O5 fertilizer 439.5 kg ha−1 with water 1778.4 m3 ha−1. The results could not only boost efficiency of water and fertilizer, but also establish the reasonable irrigation and fertilizer measure, and regulate yield of sugarcane. It could offer some ideas and techniques for developing precision farming.